Preservice Teacher’s Attitude Toward Problem-Solving in Mathematics Education - Mohammed, Atar Alphaa (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study delved into the attitudes of 90 level 300 preservice teachers towards problem-solving in mathematics education, recognising its significance in enhancing students’ mathematical proficiency. Conducted through a cross-sectional survey design, the research encompassed preservice teachers from various specialities, including Junior High School, Upper Primary, and Early Grades in a college of education in the Upper West Region of Ghana. Utilising a structured questionnaire, rate their agreement or disagreement with the 27-item attitudinal scale on a four-point scale, ranging from 1 (strongly disagree) to 4 (strongly agree). The scores were interpreted as follows: a score of one represents the lowest possible level, indicating a negative attitude, while a score of five represents the highest possible level, indicating an assertive positive attitude. The attitude scores had a standard deviation of 5.19085, suggesting moderate variability from the mean. The attitude ratings displayed a negative skewness of -0.967, indicating that most preservice teachers had predominantly favourable attitudes towards problem-solving as a teaching method. Notably, the research found no significant differences in attitudes between male and female preservice teachers, nor across different programs of study, indicating the need to consider additional factors influencing attitudes towards problem-solving in mathematics education. The lack of significant differences in attitudes based on gender or program of study suggests that factors beyond these demographic variables may influence preservice teachers’ perceptions of problem-solving